Audit Sistem Informasi Aplikasi e-Payment Menggunakan Framework Cobit 5 - Ismail Hasan; Daning Nur Sulistyowati (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
This research was carried out to identify and ensure that existing system procedures in Cimanggis District function properly using the Cobit 5 framework in auditing the e-payment application information system. Based on an audit of the e-payment application information system collected using a quantitative capability analysis method, after a thorough evaluation of the e-payment application, from the questionnaire data it can be concluded that the domain with the highest score, namely the DSS01 Manage Operations domain, has a total maturity index value of 7 .89 maturity level value 1.58 percentage value 158% with Fully Achieved achievement value and GAP value (0.42), DSS02 Manage Service Request and Incidents, got a total maturity index value of 7.87, got a maturity level value of 1.12 percentage value of 112%, with a Fully Achieved achievement value and GAP value (0.88), DSS03 Manage Problems, got a total manturity index value of 7.22, got a maturity level value of 1.44, a percentage value of 144%, with a Fully Achieved achievement value and the GAP value (0.56), with a level 2 target, namely Repeatable but Intuitive, it must be corrected in the domain and sub-domain used, and if there are problems, they must be repaired immediately.